Study of the Acoustic Suitability of an Open Plan Office Based on STI and DL2 Simulations - PASSERO, Carolina Reich Marcon; ZANNIN, Paulo Henrique Trombetta (Archives of Acoustics, 2012)
Many business offices around the world are organized as open plan offices. Therefore, studies aboutthe acoustic comfort of the people who work in them have become increasingly important. The focus ofthis work is the acoustic evaluation of an open plan office combining several architectural characteristicsand levels of ambient noise. This evaluation was performed through a computational model calibratedfrom a real office. The rate of spatial decay of sound pressure levels per distance doubling (DL2) and thespeech transmission index (STI) were simulated for the acoustic evaluation of the office, allowing for thedetermination of the radius of distraction (rD). These parameters were simulated for 6 situations usingdifferent floor and ceiling covering materials and inserting or withdrawing screens between workstations.In addition, STI and rD were simulated under two conditions of ambient noise. The results indicated thatthe DL2 and rD are adequate acoustic parameters for the acoustic evaluation and improvement of an openplan office. The DL2 was strongly influenced by the presence or absence of screens between workstationsand by the ceiling covering material. The rD was more sensitive to changes in ambient noise.